2019
DOI: 10.1021/acs.jpcc.9b05510
|View full text |Cite
|
Sign up to set email alerts
|

Structure and Dynamics of an Ionic Liquid Mixture Film Confined by Mica

Abstract: In a recent article (J. Phys. Chem. C 2019, 123, 4914−4925) we studied using molecular dynamics simulations the structure of an ionic liquid (IL) mixture comprised of 1-methyl-3octylimidazolium octylsulfate and 1-ethyl-3-methylimidazolium ethylsulfate confined by vacuum interfaces. At these interfaces, the mixture formed an apolar blocking layer concealing the smaller and more polar ions to the interior of the liquid phase. In the current work, and for the same IL mixture, we study the case of confinement betw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 69 publications
0
9
0
Order By: Relevance
“…All atoms in the crystal were taken as neutral except when surfaces were charged at the location of the terminal CH 2 groups. The protocol we used for the equilibration of our systems, described in section , is similar to the one we used for mica at the interface of an IL in ref ; detailed information about final system sizes are provided in Table S.1. Even when considering the several approximations made to model these systems, and to the best of our knowledge, this is still one of the most realistic studies to date for ionic melts at neutral and charged interfaces since all atomic and ionic positions are treated explicitly and considered for our reflectivity calculations and electrical potential analysis.…”
Section: Methodology Derivations and Computational Protocolmentioning
confidence: 99%
“…All atoms in the crystal were taken as neutral except when surfaces were charged at the location of the terminal CH 2 groups. The protocol we used for the equilibration of our systems, described in section , is similar to the one we used for mica at the interface of an IL in ref ; detailed information about final system sizes are provided in Table S.1. Even when considering the several approximations made to model these systems, and to the best of our knowledge, this is still one of the most realistic studies to date for ionic melts at neutral and charged interfaces since all atomic and ionic positions are treated explicitly and considered for our reflectivity calculations and electrical potential analysis.…”
Section: Methodology Derivations and Computational Protocolmentioning
confidence: 99%
“…From the modeling perspective, the most effort was associated with determining the diffusion parallel to the pore IL. [137][138][139][140] Given that the symmetry of the system is preserved over this axis, self-diffusion coefficients may be obtained from mean square displacement (Einstein approach) [141] or the velocity autocorrelation function (Green-Kubo formalism). [142] It was shown that ions at the solid-liqud interface may strongly coordinate with particular moieties on the surface, which may impede their free diffusion (see Figure 6a).…”
Section: Transport In the Il-filled Porementioning
confidence: 99%
“…The interfacial structure of C[2]-mim + /NTf 2 – at a sapphire surface was also investigated by using X-ray reflectivity in conjunction with MD simulations . Our group has also investigated ILs under confinement , using MD simulations, and in ref we developed the peaks and antipeaks analysis for reflectivity; the ideas introduced in ref were later expanded and applied to the study of diamond-confined molten alkali chloride salts . The literature on the structure of ILs using other surface sensitive techniques is vast, and a full set of citations is beyond the scope of this work, but particularly important has been the pioneering work by Baldelli et al using sum frequency generation as well as Perkin et al , and Atkin et al using force microscopy. …”
Section: Introductionmentioning
confidence: 99%